2012
DOI: 10.1002/elps.201200127
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretically mediated microanalysis for characterization of the enantioselective CYP3A4 catalyzed N‐demethylation of ketamine

Abstract: Execution of an enzymatic reaction performed in a capillary with subsequent electrophoretic analysis of the formed products is referred to as electrophoretically mediated microanalysis (EMMA). An EMMA method was developed to investigate the stereoselectivity of the CYP3A4-mediated N-demethylation of ketamine. Ketamine was incubated in a 50 μm id bare fused-silica capillary together with human CYP3A4 Supersomes using a 100 mM phosphate buffer (pH 7.4) at 37°C. A plug containing racemic ketamine and the NADPH re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Then, the electrical field is turned‐off so that the reaction continues at zero‐potential for a definite time known as wait time ( t wait ) during which ADP will have enough time to accumulate. The reactants will also continue to mix due to diffusion . The merge time and the wait time were experimentally optimized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the electrical field is turned‐off so that the reaction continues at zero‐potential for a definite time known as wait time ( t wait ) during which ADP will have enough time to accumulate. The reactants will also continue to mix due to diffusion . The merge time and the wait time were experimentally optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the difficulty of mixing more than two reactants by using an electric field as well as the unfeasibility of mixing reactants with identical or very close mobilities. Thus, for mixing three reactant plugs, the mixing process is triggered by the electric field (EMMA) and reactants are then allowed to diffuse at zero‐potential , during a wait time where the product will accumulate . This is the zero‐potential amplification approach .…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, on-line mixing was achieved by injecting reactants of different pH values into the capillary using a series of small hydrodynamic injections. With this approach, an enzyme buffered at pH of 7.4 was combined with a separation medium buffered at pH of 2.5 [30,31]. The parabolic shape of consecutive injections, which was a result of the laminar flow, caused each injection band to blend with the surrounding injection bands.…”
Section: Adapting the Separation To Determine Km Valuesmentioning
confidence: 99%
“…The mixing of reactants occurs by transverse diffusion, where reactants diffuse towards the wall of the capillary. As a result, this injection mode can be utilized to mix multiple injected reactants for enzymatic reactions where the pH of the enzyme reaction was different than that of the background electrolyte [30,31,41]. …”
Section: Adapting the Separation To Determine Km Valuesmentioning
confidence: 99%
“…The on‐line CE methods for investigation of in vitro drug metabolism implemented from 2002 to 2012 have been summarized by Nowak . Recently, an EMMA method was developed to investigate the stereoselectivity of the CYP 3A4‐mediated N ‐demethylation of ketamine . Partial filling of two incubation buffer plugs was used to protect enzyme and substrates from the pH of the separation buffer as well as the chiral selector in it.…”
Section: In‐capillary Assaymentioning
confidence: 99%